Developments in the health situation in Germany during the initial stage of the COVID-19 pandemic for selected indicators of GEDA 2019/2020-EHIS - Stefan Damerow; Alexander Rommel; Franziska Prütz; Ann-Kristin Beyer; Ulfert Hapke; Anja Schienkiewitz; Anne Starker; Almut Richter; Jens Baumert; Judith Fuchs; Beate Gaertner; Stephan Müters; et al. (Journal of Health Monitoring, 2020)
SARS-CoV-2, the novel coronavirus, has posed major challenges in Germany in 2020. It is unclear whether the pandemic and containment measures will have an impact on the health of the population beyond the point of infection. The German Health Update (GEDA 2019/2020-EHIS) is a nationwide survey of the population aged 15 years and older (n=23,001) that was conducted between April 2019 and September 2020. The focus of the analysis was on indicators for which pandemic-related changes could be expected. Based on regression models, adjusted proportions and mean values were estimated as trends over time. Any differences in the values found for the time period of containment measures in spring 2020 and the reference period 2019 were statistically tested. Since the implementation of containment measures, both body weight and body mass index (BMI) have increased. The utilisation of general and specialist medical services decreased temporarily. The number of tobacco smokers during the observation period also decreased, yet without revealing a clear link to the pandemic situation. No differences were found in the general population for depressive symptoms and household assistance received and provided. During the period of containment measures, changes to the health situation beyond the occurrence of infections can be observed. However, a more differentiated explanation of these findings will require further analyses.